Univalence Criteria for Two Integral Operators - Laura Filofteia Stanciu; Daniel Breaz (Abstract and Applied Analysis)
We study the univalence conditions for two integral operators to be univalent in the open unit disk. Many known univalence conditions are written to prove our main results.